2022
DOI: 10.1111/fcp.12837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sacubitril/valsartan on cognitive impairment in colchicine‐induced Alzheimer's model in rats

Abstract: Alzheimer's disease (AD) is a complex neurodegenerative disease. There is epidemiological evidence that heart failure (HF) patients are at higher risk of developing AD, and the impact of sacubitril/valsartan, the first angiotensin receptor-neprilysin inhibitor (ARNI) approved for HF, on cognitive functions is still controversial. To investigate the effect of sacubitril/valsartan on cognitive functions in colchicine-induced AD rat model. Forty adult male Wistar rats were equally allocated into four groups (each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Experimental study NEP inhibitors trigger AD-like diseases in mice Hüttenrauch et al 44 Experimental study LCZ696 increased Aβ concentration in the CSF but not in the brain Bavishi et al 43 Experimental study LCZ696 accelerates AD progression in animals Vodovar et al 47 Experimental study Long-term effects of NEP inhibitors promote AD and late-onset axonal polyneuropathy Auer-Grumbach et al 41 Experimental study LCZ696 increases AD risk compared with valsartan alone in rats El-din Hussein et al 48 Experimental study LCZ696 accelerates colchicine-induced cognitive impairment in rats Hammadi El-din Hussein et al 50 Preclinical studies LCZ696 has a neuroprotective effect by inhibiting homocysteine-induced BBB injury…”
Section: Study Type Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental study NEP inhibitors trigger AD-like diseases in mice Hüttenrauch et al 44 Experimental study LCZ696 increased Aβ concentration in the CSF but not in the brain Bavishi et al 43 Experimental study LCZ696 accelerates AD progression in animals Vodovar et al 47 Experimental study Long-term effects of NEP inhibitors promote AD and late-onset axonal polyneuropathy Auer-Grumbach et al 41 Experimental study LCZ696 increases AD risk compared with valsartan alone in rats El-din Hussein et al 48 Experimental study LCZ696 accelerates colchicine-induced cognitive impairment in rats Hammadi El-din Hussein et al 50 Preclinical studies LCZ696 has a neuroprotective effect by inhibiting homocysteine-induced BBB injury…”
Section: Study Type Findingsmentioning
confidence: 99%
“…Valsartan can decrease the risk of AD development as it selectively blocks AT 1 R as RAS inhibitors have been associated with the reduction of brain damage in different experimental and clinical models of neurodegenerative diseases 49 . In addition, LCZ696 extravagant colchicine‐induced cognitive impairment in rats by increasing Aβ accumulation, oxidative stress and inflammation compared to valsartan alone 50 . Hence, LCZ696 triggers a deleterious effect on cognitive impairment in the colchicine‐induced AD rat model.…”
Section: Nep Inhibitors In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Still, regarding this class of drugs, we can highlight corticosteroids and colchicine. Corticosteroids can cause weight gain, generating metabolic problems and fluid retention, compromising hemodynamic, cardiovascular, and renal functions [ 19 ], while colchicine can cause gastrointestinal complications and a reduction in circulating neutrophils, and high doses can cause aplastic anemia by inhibiting erythroid precursor mitosis and increase the risk of developing Alzheimer’s disease [ 20 ]. The most widespread hyperuricemia inhibitors are the xanthine oxidase inhibitorallopurinol and the uricosuric agent probenecid, which inhibit the reabsorption of urates at the level of the proximal convoluted tubule, and seeks to bring the serum uric acid level below 6 mg/dL (357 µmol/L).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a low concentration of Colc (1.2 mg per day) causes a reduction in pain and gout symptoms, whereas a high dose of Colc (4.8 mg over 6 h) can cause common side effects, such as gastrointestinal upset including nausea, diarrhea, vomiting, low blood cell count, and rhabdomyolysis, as well as bone marrow damage, anemia, and hair loss. Colc causes oxidative stress in animals, leading to cognitive impairment, and its therapeutic use has been linked to sporadic Alzheimer’s disease in humans [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%